Assessment of a technology acquisition and assimilation methodology a case study on ABS-CBN Corporation's enterprise service management system - Laspiñas, Rhea P. (University of the Philippines Diliman, 2015)
ABS-CBN Corporation launched a technology acquisition and assimilation initiative to implement an industry best-practice Enterprise Service Management System to align with the company's strategic plans and objectives in transforming the lives of its internal and external customers. The Enterprise Service Management System (ESMS) technology solution consolidated the service management and common processes of different companies and business units (ABS-CBN IT, ABS-CBN Global IT, ABS-CBN Convergence IT and ABS-CBN Shared Services) under a single ticketing platform, that can monitor IT assets and manage software licenses, improve availability and security of mission critical services, and manage processes through automated workflows that would result to faster turnaround time.